A year's experience with a mobile coronary resuscitation unit. Issue 5677 (25th October 1969) - Dewar, H. A.; McCollum, J. P. K.; Floyd, M.
Abstract : A mobile unit for the emergency treatment of cases of coronary thrombosis in the patient's home and for their supervised conveyance to hospital has been operating in the City of Newcastle upon Tyne for a year. In that time 134 cases have been attended, and of these 39 benefited appreciably from use of the unit. The value of such a unit must be balanced in relation to the current mortality of the disease outside and inside hospital and the staff available